Philippine major hog/sow - Philippine Statistical Association-Agribusiness System for Statistical Information Services and Technology (Quezon City Philippine Statistical Association (PSA)-Agribusiness System for Statistical Information Services and Technology (ASSIST), 1995)
Contents: List of independent hog raisers, contract growers, and advertisers. Indices to independent hog raisers.
Purpose: A directory of commercial hog farms in the Philippines. This book is the first of the agribusiness directories being prepared and maintained by the Philippine Statistical Association's ASSIST project. Its contents are listed alphabetically, and sorted by farm name and province. It provides farm information such as its name address, contact details, production levels, and more.
Keywords: Swine breeders -- Directories; Pork industry and trade -- Philippines; Swine -- Equipment and supplies -- Directories